The Influence of Financial Capabilities, Convenience and Security on the Behavior of Fund E-Wallet User Systems - Kevin Deyan Zanroni; Eska Prima Moiuque D; Nenden Restu Hidayah (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
The purpose of this research is to determine the influence of Brand The purpose of this research is to determine the influence of financial capability, convenience and security on the behavior of e-wallet fund users. This type of research is quantitative. The data collection method in this research used a questionnaire technique, with a sample of 130 respondents. The research results show that multiple linear regression Y = 21,295 + 0,140 X1 + 0,336 X2 + 0.123 X3 + 3,536. Where the coefficient is positive, meaning that there is a positive or unidirectional relationship between the variables financial capability (X1), convenience (X2) security (X3), the value is 0 (zero), on the behavior (Y) of the e-wallet user system and the value is 21,334. The results of the research show that the results of the research show that the financial capability test (XI) shows tcount 2,655 > ttable 1,978 and significance 0.000 < 0.05, so the results of the hypothesis Ha are accepted and Ho is rejected, meaning that financial capability has a positive and significant effect on user system decisions e -wallet funds. The results of the convenience test (X2) show that tcount is 6,262 > ttable 1,978 and the significance is 0.000 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that convenience has a positive and significant effect on the system decisions of fund e-wallet users. The results of the security test (X3) show tcount 2,517 > ttable 1,978 and significance 0,013 < 0,05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that security has a positive and significant effect on system decisions for e-wallet fund users. Based on the comparison of the Fcount value with Ftable, the Fcount value is greater than the Ftable value, namely 18,608 > 2,44, so it is concluded that accepting the hypothesis, meaning that there is a simultaneous influence between the allegations proposed in this F test is "there is an influence of financial capability (X1), convenience ( X2) security (X3), on the behavior (Y) decisions of the fund e-wallet user system. This can be seen at the significance level of 0,000 <0,05..